Externality-correcting taxes and regulation - Vidar Christiansen; Stephen Smith (Center for Economic Studies and ifo Institute (CESifo), 2009)
Much of the literature on externalities has considered taxes and direct regulation as alternative policy instruments. Both instruments may in practice be imperfect, reflecting informational deficiencies and other limitations. We analyse the use of taxes and regulation in combination, to control externalities arising from individual consumption behaviour. We consider cases where taxes are either imperfectly differentiated to reflect individual differences in externalities, or where some consumption escapes taxation. In both cases we characterise the optimal instrument mix, and show how changing the level of direct regulation alters the optimal externality tax.
Keywords: H21; H23; 330; externalities; Pigouvian taxes; regulations; Internalisierung externer Effekte; Verbrauchsteuer; Regulierung; Policy-Mix; Theorie